2011
DOI: 10.1111/j.1943-278x.2011.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital Breakdown, Shame, and Suicidality in Men: A Direct Link?

Abstract: The influence of feelings of shame originating from marital breakdown on suicidality is examined. The role of mental health problems as probable mediating factors is also considered. Internalized shame, state (related to separation) shame, and mental health problems were significantly correlated with the score for suicidality during separation in both genders. Tested structural equation model indicated that internalized shame was not directly linked to suicidality, but was mediated either by state shame or men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Thus, it is perhaps not surprising that maladaptive perfectionists may be driven by an urge to end the feeling of shame (Tangney, 2002). This is consistent with general findings about the relationship between shame and suicidality (Foster, 2003;Hastings, Northman, & Tangney 2000;Kö lves, Ide, & De Leo, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, it is perhaps not surprising that maladaptive perfectionists may be driven by an urge to end the feeling of shame (Tangney, 2002). This is consistent with general findings about the relationship between shame and suicidality (Foster, 2003;Hastings, Northman, & Tangney 2000;Kö lves, Ide, & De Leo, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…For men, the exception to this may be in the context of romantic relationships (e.g., Jennings & Murphy, 2000), and research suggests that in comparison to females, males may be more vulnerable to the effects of relationship problems, with recently separated men being more likely to engage in maladaptive coping responses (Moore, Rice, & Fallon, 2010). Furthermore, shame has recently been implicated in this process (Kolves, Ide, & De Leo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also proposed that shame may mediate the link between mental health problems and suicidal behaviour among individuals experiencing relationship separation (e.g., Kolves, Ide, & De Leo, 2011). While the directionality of these relationships is yet to be confirmed, evidence is mounting for the role played by shame in serious psychopathology and further research is warranted on the negative consequences of shame within the context of intimate relationships.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 96%
“…In general, research supports a positive association between being single and suicide rates. The association appears stronger if we consider divorce and-especially-separation [18,19]. A study found separated men to be about six times more likely to die from suicide than their married counterpart [20].…”
Section: Unmodifiable Risk Factorsmentioning
confidence: 99%
“…Also, women would generally benefit from far greater social networks than men, and this would offer both support for emotional ventilation and opportunity for new relationships [19].…”
Section: Unmodifiable Risk Factorsmentioning
confidence: 99%